Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Pertumbuhan Ekonomi Melalui Pengeluaran Pemerintah di Kalimantan Selatan - Rangga Gotama Mastomo; Saipudin; Yunita Sopiana; Anshar Nur; Noor Rahmini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the influence of Local Own-Source Revenue and Intergovernmental Fiscal Transfers on Economic Growth through Government Expenditure in South Kalimantan Province from 2014 to 2022. Employing a quantitative approach with descriptive and associative analysis, the research utilizes path analysis techniques within the PLS-SEM method, using SmartPLS 3 software. The findings reveal that Local Own-Source Revenue significantly and positively impacts Economic Growth, indicating that increases in Local Own-Source Revenue stimulate economic growth in South Kalimantan. Similarly, Intergovernmental Fiscal Transfers also significantly and positively affect Economic Growth, underscoring their crucial role in supporting the regional economy. However, an intriguing outcome of this study is the significant negative impact of Government Expenditure on Economic Growth. This suggests that while government spending increases, if not allocated efficiently, it can actually impede economic growth. Furthermore, the study indicates that Local Own-Source Revenue and Intergovernmental Fiscal Transfers allocated through Government Expenditure have a significantly negative indirect effect on Economic Growth. This means that although Local Own-Source Revenue and Intergovernmental Fiscal Transfers enhance the fiscal capacity of local governments, the effectiveness of government spending is the primary determinant of their impact on economic growth.